How Can a Country 'Graduate' from Procyclical Fiscal Policy? Evidence from China - Clemens Fuest; Jing Xing (Center for Economic Studies and ifo Institute (CESifo), 2015)
In this study, we analyze the cyclicality of fiscal policies in China during the period 1978-2013. We find that the cyclicality of local government spending in China significantly affects the cyclicality of total government spending. By employing both time-series and province-level panel data, we show that local budgetary government spending was strongly procyclical during the 1980s, but it became counter-cyclical with respect to nationwide output fluctuations and acyclical with respect to region-specific output shocks since the mid-1990s. We argue that these are likely to be consequences of the 1994 fiscal reform, which revamped the fiscal relations between the central and local governments, reduced the procyclicality of local government budgetary revenue and brought in counter-cyclical intergovernmental transfers. Findings of this study contribute to the debate on how developing and emerging countries, in particular those with federal fiscal structures, could reduce the procyclicality of their fiscal policies.
Keywords: H71; H72; H77; 330; fiscal federalism; tax reform; government spending